Analysis of COVID-19 Surveillance System at Makassar City Health Office 2020 - Fatmasari; Syahrul, Fariani; Darajat , Zakiah; Kusuma, Eva Flourentina (Indonesian Journal of Tropical and Infectious Disease, 2022)
One of the infectious diseases that emerged in Indonesia in 2020 has been designated as a COVID-19 pandemic since March 11, 2020, and until now, the pandemic has not been completed. Surveillance has a role in providing information on targeted disease control activities; analyzed the COVID-19 surveillance system based on the current system approach at the Makassar City Health Office. Methods This research is a descriptive observational study conducted in September-October 2020. Data collection was carried out using in-depth interviews with people who were key informants of COVID-19 surveillance activities. There are four informants in this study. In addition, secondary data was obtained from the P2P field regarding COVID-19 cases. In general, the Input component has not been fulfilled; HR has multiple tasks, the job desk is irregular, and several important forms are not used in the methods section. The process component has been running but has not been maximized because there are still incomplete data, no reports based on the PE form, the All-Record TC-19 information system has not been used, and data analysis is still incomplete, data analysis is not equipped with data interpretation. In the Output component, the success rate for public health surveillance criteria has not been evaluated, and the dissemination of information has been carried out well across sectors. The implementation of COVID-19 surveillance at the Makassar City Health Office has been carried out well, but some things are still not optimal.